Factors affecting language acquisition in the digital switch - Minh, Trần Quang (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
These aspects motivational and affective effects of language learning have largely been neglected by researchers despite having a monumental influence on the acquisition of language. For this paper, I would like to address the roles of motivation and affective effects on second language acquisition by addressing the following questions: 1) What are the roles of motivation and affective effects in language acquisition? 2) What are the triggers of these effects and how they affect students learning process? 3) What can teachers do to raise or alleviate these effects for the betterment of language learning? For the first question, this paper will explore the role of motivation in language acquisition by using citations from Celce-Murcia, Brinton, & Snow (2014), Meniado (2019), Dörnyei, Z. (1990), etc. To answer the second question, the paper will discuss the prompts and input for various affective effects and their influence on students through Garrett & Young (2009). The effects on language would also be discussed using study by Pavlenko & Dewaele (2004), Dewaele (2005), Tran, Thu H. (2013) etc. For the final question, the paper will provide suggestions and approaches to address the motivational and affective elements of language acquisition from Celce-Murcia, Brinton, & Snow (2014) as well as tasks and strategies to raise motivation from both teachers and students Dörnyei (2003).